Bosnia and Herzegovina : Technical Assistance Report-Government Finance Statistics Mission. (IMF Staff Country Reports; Country Report ;, 2018)
This Technical Assistance Report discusses the recommendations made by the IMF mission to assist the statistical authorities of Bosnia and Herzegovina (BiH) with setting up a register of public sector units and further enhancing the debt data based on the framework of the Government Finance Statistics Manual 2014 and European System of National and Regional Accounts. It is recommended that the three statistical institutes (BiH Agency for Statistics, Institute of Statistics, and the Institute of Statistics of the Federation of BiH) should draw up a provisional list of government controlled entities before the sectorization project starts in October 2015. The list should comprise all entities where government exercises some influence.